Involvement of the Retinoid X Receptor Ligand in the Anti-Inflammatory Effect Induced by Peroxisome Proliferator-Activated Receptor 𝜸 Agonist In Vivo - Atsuki Yamamoto; Hiroki Kakuta; Hiroyuki Miyachi; Yukio Sugimoto (PPAR Research)
Peroxisome proliferator-activated receptor γ (PPARγ) forms a heterodimeric DNA-binding complex with retinoid X receptors (RXRs). It has been reported that the effect of the PPAR agonist is reduced in hepatocyte RXR-deficient mice. Therefore, it is suggested that the endogenous RXR ligand is involved in the PPARγ agonist-induced anti-inflammatory effect. However, the participation of the RXR ligand in the PPARγ-induced anti-inflammatory effect is unknown. Here, we investigated the influence of RXR antagonist on the anti-inflammatory effect of PPARγ agonist pioglitazone in carrageenan test. In addition, we also examined the influence of PPAR antagonist on the anti-inflammatory effect induced by RXR agonist NEt-3IP. The RXR antagonist suppressed the antiedema effect of PPARγ agonist. In addition, the anti-inflammatory effect of RXR agonist was suppressed by PPARγ antagonist. PPARγ agonist-induced anti-inflammatory effects were reversed by the RXR antagonist. Thus, we showed that the endogenous RXR ligand might contribute to the PPARγ agonist-induced anti-inflammatory effect.